(untitled) (Psicologia USP, 2016)
Axel Honneth associates his reading of Hegel with Winnicott's maturational development theory, in order to defend theses on intersubjectivity and recognition. That connection between philosophy and psychoanalysis is a target of criticism from two Hegelians: Joel Whitebook, a reader of Freud, and Judith Butler, a critical reader of Freud and Lacan. At the core of the controversy is Honneth's rejection of the work of the negative that is performed by Freud's death drive. We intend on following in the wake of that debate, and thus investigate the reasons and consequences for social criticism of Honneth's rejection of Freud's death drive.